2011
DOI: 10.1111/j.1526-4610.2011.02014.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute Striatal Necrosis in Hemiplegic Migraine With de Novo CACNA1A Mutation

Abstract: We report the case of a 9-year-old girl with early-onset developmental delay, chronic ataxia and prolonged hemiplegic migraine episodes bringing about progressive deterioration. Two days into one episode, diffusion-weighted magnetic resonance imaging disclosed unilateral striatal abnormal signal consistent with cytotoxic edema, which evolved into atrophy on follow-up scans. Mutational screen of CACNA1A gene identified a de novo p.Tyr1387Cys mutation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 14 publications
(22 reference statements)
0
14
0
Order By: Relevance
“…In parallel with the concept of degeneration caused by sodium overload, ictal cytotoxic edema during the long-lasting depolarization (spreading depression) has been frequently reported in FHM (for example Chabriat et al, 2000; Butteriss et al, 2003) and has been suggested to sustain the long-lasting aura (Iizuka et al, 2006) and contribute to neurodegeneration (Carreño et al, 2011). Likewise, ictal edema is associated with neuronal degeneration and sclerosis of the hippocampus in FSs (Scott et al, 2003, 2006; Sokol et al, 2003).…”
Section: Sodium Overload Cytotoxic Edema and Tissue Degenerationmentioning
confidence: 94%
“…In parallel with the concept of degeneration caused by sodium overload, ictal cytotoxic edema during the long-lasting depolarization (spreading depression) has been frequently reported in FHM (for example Chabriat et al, 2000; Butteriss et al, 2003) and has been suggested to sustain the long-lasting aura (Iizuka et al, 2006) and contribute to neurodegeneration (Carreño et al, 2011). Likewise, ictal edema is associated with neuronal degeneration and sclerosis of the hippocampus in FSs (Scott et al, 2003, 2006; Sokol et al, 2003).…”
Section: Sodium Overload Cytotoxic Edema and Tissue Degenerationmentioning
confidence: 94%
“…In episodic CACNA1A disorders, the most common finding was a developmental delay after a normal birth and an unremarkable neonatal period (25 FHM1 and 10 EA2 pedigrees, respectively) [5,10,11,13,14,17,[19][20][21][22][23][24][26][27][28][31][32][33][34][35]. Delayed motor milestones or mental retardation were usually observed in the offspring of patients previously diagnosed with EA2 or FHM1, before the onset of episodic symptoms.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…), acute striatal necrosis (Carreño et al. ), hemiplegia–hemiconvulsion–epilepsy syndrome (Yamazaki et al. ), and recurrent ischemic stroke (Knierim et al.…”
Section: Introductionmentioning
confidence: 99%
“…The allelic heterogeneity displayed by the CACNA1A gene also correlates with substantial clinical variation, as mutations in this gene are also responsible for two other autosomal dominant diseases: episodic ataxia type 2 (EA2, MIM #108500) and spinocerebellar ataxia type 6 (SCA6, MIM #183086). The range of CACNA1A-linked phenotypes has even been broadened by the recent descriptions of patients presenting with alternating hemiplegia of childhood (de Vries et al 2008), acute striatal necrosis (Carreño et al 2011), hemiplegia-hemiconvulsion-epilepsy syndrome (Yamazaki et al 2011), and recurrent ischemic stroke (Knierim et al 2011). Clinical variation is also seen within the HM phenotype, a condition in which CACNA1A may sometimes be implicated as a modifier gene rather than a disease-causing gene (Serra et al 2010).…”
Section: Introductionmentioning
confidence: 99%